A comparison of fatigue crack growth performance of two aerospace grade aluminium alloys reinforced with bonded crack retarders. Issue 5 (1st December 2017) - Syed, A.K.; Zhang, X.; Fitzpatrick, M.E.
Abstract: To improve the fail‐safety performance of integral metallic structures, the bonded crack retarder concept has been developed in recent years. This paper presents an experimental investigation on the effectiveness of bonded crack retarder on fatigue crack growth life in two aerospace aluminium alloys: 2624‐T351 and 7085‐T7651. M(T) specimens bonded with a pair of straps made of GLARE fibre‐metal laminate were tested under the constant amplitude load. Although the bonded crack retarders increased the crack growth life in both alloys, the magnitude of life improvement is very different between them. Compared to unreinforced specimens, application of crack retarders has resulted in 90% increase in fatigue life in AA7085, but only 27% increase in AA2624. The significant difference in fatigue life improvement is owing to the material's intrinsic fatigue crack growth rate property, ie, the Paris law constants C and n . Value of n for AA7085 is 1.8 times higher than that for AA2624. Therefore, AA7085 is much more sensitive to reductions in the effective stress intensity factor brought by the crack retarders, hence better life improvement.